Bonds for Sustainable Development : Impact Report 2019 - World Bank (World Bank, Washington, DC, 2020)
This World Bank Sustainable Development Bond Impact Report 2019 is the first impact report covering all World Bank (International Bank for Reconstruction and Development, IBRD) bond issuance and the entire portfolio of IBRD’s development activities. The Sustainable Development Bond Impact Report 2019 describes how IBRD bond proceeds support the financing of sustainable development across a variety of sectors and how project results align to the Sustainable Development Goals (SDGs). The report is a key part of the World Bank’s efforts to engage market participants to support capital markets with strong transparency and disclosure standards and improve market participation to direct greater capital flows to sustainable purposes. The report provides an overview of how the World Bank engages with investors when issuing Sustainable Development Bonds using the SDGs as a framework and highlights related transactions. The Impact Highlights section maps results to the SDGs for 71 IBRD projects completed in fiscal year 2019 and provides forward looking information for the 84 projects that were approved and started disbursing in fiscal years 2018 and 2019 – the period for which IBRD introduced detailed use of proceeds language for its bonds. The report also provides information on the World Bank Group’s response to the coronavirus pandemic including examples of projects in countries eligible for IBRD financing. The impact report was prepared in consultation with investors and other capital market stakeholders, as an integral part of the process, to ensure the report met investor expectations. In addition to providing information on results, the report outlines the World Bank’s operational processes and safeguards and alignment of its bond issuance with market frameworks, namely the Sustainability Bond Guidelines coordinated by the International Capital Market Association.